Aeschylus and his relation to the Greek drama - Helder, Arthur Hurschel (My University, 1904)
Introduction: Aeschylus came to suffer much from envy and ill-will. Under his burden he left Athens never to return, and settling at Gela under the Patronage of Huron, he spent the last three years of his life engaged in writing. His name will were stand among the first of those who have enriched the world by their literary art.
Citation: Helder, Arthur Hurschel. Aeschylus and his relation to the Greek drama. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Aeschylus; Drama; Greek Dramas; Greek History; Theses